2020
DOI: 10.3390/app10082807
|View full text |Cite
|
Sign up to set email alerts
|

Grating Metamaterials Based on CdTe/CdMgTe Quantum Wells as Terahertz Detectors for High Magnetic Field Applications

Abstract: The cyclotron and magnetoplasmon resonances were studied at 2 K in grating metamaterials fabricated on wafers with one or two modulation doped CdTe/CdMgTe quantum wells. The gratings (with the period varied between 2 μ m and 8 μ m) were prepared with an electron beam lithography either by etching or by evaporation of Au. The gratings were studied with an atomic force microscope which revealed a correlation between the depth and width of etched grooves at a constant time of etching. The sharpest reson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Second, we showed that we were able to generate and transmit circularly polarized radiation to the sample cooled to a low temperature, which is confirmed by the red curve in Figure 6. Third, based on earlier studies on magnetoplasmons in CdTe-based QWs [25][26][27], we state that the resonances observed in Figure 6 on the etched sample were due to the excitation of a magnetoplasmon, which appeared not to be circularly polarized.…”
Section: Discussionmentioning
confidence: 66%
“…Second, we showed that we were able to generate and transmit circularly polarized radiation to the sample cooled to a low temperature, which is confirmed by the red curve in Figure 6. Third, based on earlier studies on magnetoplasmons in CdTe-based QWs [25][26][27], we state that the resonances observed in Figure 6 on the etched sample were due to the excitation of a magnetoplasmon, which appeared not to be circularly polarized.…”
Section: Discussionmentioning
confidence: 66%
“…The estimated detector response to free-space illumination scaled quadratically with plasmon quality factor, and promised sensitive detection for practically important terahertz range [11]. The idea ignited a booming research in the field of 2d plasmon-enhanced detectors, with further proposals based on different materials [12][13][14][15][16][17], rectification mechanisms [18][19][20][21], and coupling schemes [22,23].…”
Section: Introductionmentioning
confidence: 99%